Understanding Consumer Behavior in Online Education: Factors Influencing Purchase Intention of Paid Online Course - Amalia, Hanif Mentari; Belgiawan, Prawira Fajarindra (Syntax Corporation, 2025)
The evolution of technology has significantly influenced educational methodologies, leading to a surge in the popularity of online learning platforms. This study aims to investigate the factors influencing the purchase intentions of paid online courses in Indonesia. Utilizing a quantitative research design, the study examines the impact of several variables: certificate, performance expectation, perceived lecturer expertise, testimonial, brand trust, perceived financial cost, and personal trial experience on the decision-making process of consumers considering paid online courses. Variables examined in this research was obtained from the previous research and preliminary research to confirm the importance of these variables. Sample used in this research are 237 respondent that fit the criteria of having experience in using Online Paid Course, since this resarch used judgmental sampling. Data are gathered using questionnaire and analyze using SPSS 27.0. The findings reveal that perceived lecturer expertise and personal trial experience significantly enhance purchase intentions, underscoring the importance of credible instructors and the opportunity for prospective students to experience courses before enrollment. Perceived financial cost also plays a critical role, indicating that cost-effective pricing strategies are essential for attracting and retaining learners. Some group with different motivation and type has different important variable for them. Future research are recommended to explore on more specific themes like career switchers or detailed evaluations of an OPC provider's brand, considering user experience and other key aspects that influence brand perception and purchase decisions in the evolving field of online education.